Dancing with Epistemic Borders: Knowledge and unknowns in mixed-methods Practice-as-Research (PaR) collaborations between dance and social science. (19th May 2021) - McGrath, Aoife; Durrer, Victoria; Campbell, Peter
Abstract : This article explores an encounter with 'unknowns' of knowledge production and analysis experienced by a dance practitioner-scholar and social science researchers during an ongoing, collaborative project charting the effect of territorial borders on dance artists' lives and practice. Expanding the investigation of borders beyond the territorial to also encompass the methodological, the Co-Motion: Dance and borders project experiments with how improvised dance responses to research questions place an affective and embodied experience of borders in dialogue with more traditional methods of sociological enquiry. In contrast to 'Danced Data' projects that position dance as a primarily interpretative and communicative tool, Co-Motion considers how dance practice can be made integral to interdisciplinary, mixed-methods research processes as a source of knowledge production in its own right. The project's aim to achieve an interweaving of different knowledges through a possible fusion of horizons in an event generated by a joint questioning (Gadamer) seemed a relatively straightforward premise at the outset. However, the practical execution raised questions as to how a mixed-methods approach might truly embrace epistemological pluralism in knowledge production from inception, and how seemingly paradoxical forms of knowledge generation and languaging (Ingold) might be reconciled in analysis. Acknowledging these complexities, this article presents a dialogue between the researchers involved, mapping a terrain that welcomes unknowns and challenges the knowledge hegemonies experienced. Building on Mignolo and Tlostanova's (2006) critique of Western imperial and colonial knowledge hierarchies and their concept of 'critical border thinking', we ask how dance troubles epistemic frontiers that place knowledge classified as other outside of discourse. We also consider what epistemic shifts need to occur in collaborative, interdisciplinary projects to enable an 'unlearning and ungrounding of knowledge' that allows 'unforeseen bodies, movements and relations' (Cvejić, 2018, p.226) to inform the design of cultural policies that impact artists' daily lives and practice.